A critical discourse analysis of Vandana Shiva's environmental and normative discourse : social representations and identity of seeds - (:unkn) unknown (Università della Calabria, 2019)
Despite globalization claims to benefit all communities around the globe, it ‘provides opportunities only for a global elite’ (Kramsch/Boner 2010). This kind of analysis aims at unveiling the correlations in discourse between language and the environment. Critical discourse analysis can disclose the ways in which language plays a key role in environmental issues both at the local and global levels. One crucial aspect which can be taken into account by critical discourse analysis is that of social representations embedded in hegemonic representational systems and which can be countered by alternative environmental discourses. In the field of discourse analysis, social representations can be considered ‘as constituting, reproducing, challenging and restructuring systems of knowledge and belief’ (Fairclough 1992: 168). This research project focuses on how environmental discourse is shaped to counter the global industrialized modern world in defence of the environment. In particular, the analysis revolved around normative and environmental discourse. Two documents which were written with the intent to regulate seeds and a collection of Shiva’s texts were used as the materials to carry out critical discourse analysis which ultimately focuses on exploiting new discursive representations for a more sustainable environment. Emphasis is specifically placed on how the social reality of ‘seed’ can be reconstructed from a natural environmental perspective. The mixed method research design adopts an interdisciplinary approach which draws on Corpus Linguistics, Critical Discourse Analysis and the Social Representations Theory (Moscovici 2000) to uncover the socio-cognitive communicative mechanisms that contribute to the reconstruction of Shiva’s environmental worldviews within contemporary globalized social reality. In particular, findings show how Shiva constructs and portrays the identity and social representations of ‘seeds’ which is not influenced by the hegemonic dominant discourse and which fosters an alternative practice of environmental discourse. The language of ecology and the discursive constructions featuring Shiva’s counter-discourse are chosen to shape representations or re-representations which allow the audience to picture an alternative social reality of the surrounding environment. Overall, the analysis suggests how Shiva’s discourse is driven by the purpose of preserving the Earth’s natural ecosystem against current hegemonic forces of the contemporary globalized world.
Dottorato di Ricerca Conoscenze e innovazioni per lo sviluppo "Andre Gunder Frank". Ciclo XXVII
Keywords: Environmental Discourse; Social Representations Theory; Critical Discourse Analysis; Corpus linguistics; Environment Social Representations